Chemotherapeutic dihydromyricetin with remarkable anti-tumor activity and biosafety for muscle invasive bladder cancer - Guo, Zicheng; Wang, Wang; Hu, Weikang; You, Wenjie; Wang, Zijian (Frontiers in Pharmacology, 2025)
Plant-derived drugs (PDD) with remarkable anti-tumor activity and biosafety are highly desirable for clinical tumor chemotherapy. In this work, dihydromyricetin (DHM), a natural PDD extracted from ratten tea, was screened out to be a potential chemotherapeutic drug for muscle invasive bladder cancer (MIBC). The results of in vitro assays confirmed that DHM could effectively inhibit the proliferation, survival and migration of MIBC cells, and promote apoptosis (P < 0.05). M1 macrophage polarization was also observed after DHM chemotherapy. The hub genes in cell cycle and apoptosis signaling pathways were differential expressed, and the epithelial-mesenchymal transition (EMT) in MIBC cells was also reversed by DHM treatment. The in vivo effectiveness and biosafety evaluations of DHM chemotherapy were performed using a xenograft bearing mice model. The results revealed that DHM intravenous chemotherapy with a dose of 20 mg/kg for 7 times could significantly suppress the in vivo tumorigenesis of MIBC (P < 0.05), while triggered no obvious drug side effects. In conclusion, this work provided a PPD with remarkable in vitro and in vivo anti-tumor activity and biosafety, which could serve as a promising alternative for the application of MIBC chemotherapy.